Chapter 19 Samhandling During Crisis Work A Three-Level Model - Carlström, Eric (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"Samhandling is considered as a key solution when asymmetry occurs. An expectation of seamless samhandling can be a special challenge to High Reliability Organizations which have mechanistic traditions in common, i.e. an assumption of linearity and routine-based work. In this chapter, a model to operationalize samhandling is presented. This conceptual study is based on observational data from an inter-organizational exercise. A full-scale exercise of a train accident on the Öresund Bridge between Sweden and Denmark was observed. The overall goal of the exercise was to effectively solve the situation. However, different routines contributed to confusion and misunderstandings in the meeting on how to act. The exercise was dominated by a focus on linearity within the internal organizations, which hindered samhandling. In order to conceptualize samhandling, a three-level model is presented. It consists of "sequential samhandling", i.e. a simplified, assembly-line type work process, "parallel samhandling", i.e. carrying out tasks simultaneously, and "synchronous samhandling", i.e. tasks performed at the same time in a spontaneous and natural way. A three-level samhandling model such as the one presented can be a useful tool for managing disasters."